Incomplete vaccination in children under 2 years of age at the Tulcán Sur Health Center - Guerrón Enríquez, Sara Ximena; Narváez Jaramillo, Melba Esperanza; Sigcha Báez, Julio César; Morillo Cano, Julio Rodrigo (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
Vaccination campaigns are carried out worldwide with a process of great importance in disease prevention. Within the population, children under two years of age are a priority and are part of the first vaccination schedules that are developed. The research analyzed the situation of the children of Tulcán Sur in 198 families. To obtain results, theoretical and empirical methods were used, where the application of a survey made it possible to obtain various data of interest for the analysis. The results show the existence of a low education even on the knowledge and mastery of the importance of vaccines, which together with the economic situations and remoteness in several cases, cause an incomplete vaccination schedule in a significant number of children under two years. This situation shows the need to achieve broader and more systematic work by health personnel on the population in order to achieve greater participation in vaccination processes with emphasis on children under two years of age. The lack of knowledge on the part of the population about vaccines and the still existence of myths that reduce the credibility of vaccination and undermine the process and its effectiveness in preventing diseases are evident.